High-Resolution Genomic Profiling of Chromosomal Abnormalities in Human Stem Cells Using the 135 K StemArray - Aaron M. Elliott; Kristi A. Hohenstein Elliott; Anja Kammesheidt (Stem Cells International)
Culturing stem cells for an extended period of time can lead to acquired chromosomal aberrations. Determining the copy number variant (CNV) profile of stem cell lines is critical since CNVs can have dramatic effects on gene expression and tumorigenic potential. Here, we describe an improved version of our StemArray, a stem-cell-focused comparative genomic hybridization (aCGH) microarray, which contains 135,000 probes and covers over 270 stem cell and cancer related genes at the exon level. We have dramatically increased the median probe spacing throughout the genome in order to obtain a higher resolution genetic profile of the cell lines. To illustrate the importance of using the StemArray, we describe a karyotypically normal iPSC line in which we detected acquired chromosomal variations that could affect the cellular phenotype of the cells. Identifying adaptive chromosomal aberrations in stem cell lines is essential if they are to be used in regenerative medicine.